2018
DOI: 10.3389/fnhum.2018.00277
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Repetition Learning on Associative Recognition Over Time: Role of the Hippocampus and Prefrontal Cortex

Abstract: When stimuli are learned by repetition, they are remembered better and retained for a longer time. However, current findings are lacking as to whether the medial temporal lobe (MTL) and cortical regions are involved in the learning effect when subjects retrieve associative memory, and whether their activations differentially change over time due to learning experience. To address these issues, we designed an fMRI experiment in which face-scene pairs were learned once (L1) or six times (L6). Subjects learned th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 82 publications
(136 reference statements)
1
31
0
1
Order By: Relevance
“…One possibility is that participants learned new PAs three times in their study, which resulted in increased activation in the hippocampus for the schema‐IC condition, leading to comparable hippocampal activation between conditions. Studies have shown that hippocampal activation increases via repetitive learning (Zhan, Guo, Chen, & Yang, ; for a review, see Kim, ). As proposed by van Kesteren et al (), schema‐incongruent associations could be a part of schema if they were reactivated repeatedly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that participants learned new PAs three times in their study, which resulted in increased activation in the hippocampus for the schema‐IC condition, leading to comparable hippocampal activation between conditions. Studies have shown that hippocampal activation increases via repetitive learning (Zhan, Guo, Chen, & Yang, ; for a review, see Kim, ). As proposed by van Kesteren et al (), schema‐incongruent associations could be a part of schema if they were reactivated repeatedly.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that hippocampal activation increases via repetitive learning (Zhan, Guo, Chen, & Yang, 2018; for a review, see Kim, 2017).…”
Section: Hippocampus In Schema-related Memory Retrievalmentioning
confidence: 99%
“…[ 16 ] Learning and retention are better and more beneficial with brief multiple properly spaced sessions than single lengthy lessons. [ 26 27 ] Repeated exposure to personal cues is likely to motivate a person to take action and modify their health behavior. [ 14 ] Personal life-style habits of future health-care providers have been shown to affect their counseling practices to the patients.…”
Section: Discussionmentioning
confidence: 99%
“…the research assistants encouraged the mothers to access the website at least once every 2 days, considering that memory from once accessed learning might be maintained up to 24 hours [27]. In addition, they confirmed the mothers' attendance every day and measured their access rates from the initial introduction section to the final summary and wrap-up section to guarantee completion of the entire educational content.…”
Section: ) Association Between the Early Provision Of Solid Foodmentioning
confidence: 99%